The impact of CACNA1C gene, and its epistasis with ZNF804A, on white matter microstructure in health, schizophrenia and bipolar disorder1. (29th November 2016) - Mallas, E.; Carletti, F.; Chaddock, C. A.; Shergill, S.; Woolley, J.; Picchioni, M. M.; McDonald, C.; Toulopoulou, T.; Kravariti, E.; Kalidindi, S.; Bramon, E.; Murray, R.; et al.
Abstract : Genome‐wide studies have identified allele A (adenine) of single nucleotide polymorphism (SNP) rs1006737 of the calcium‐channel CACNA1C gene as a risk factor for both schizophrenia (SZ) and bipolar disorder (BD) as well as allele A for rs1344706 in the ZNF804A gene. These illnesses have also been associated with white matter abnormalities, reflected by reductions in fractional anisotropy (FA), measured using diffusion tensor imaging (DTI). We assessed the impact of the CACNA1C psychosis risk variant on FA in SZ, BD and health. 230 individuals (with existing ZNF804A rs1344706 genotype data) were genotyped for CACNA1C rs1006737 and underwent DTI. FA data was analysed with tract‐based spatial statistics and threshold‐free cluster enhancement significance correction ( P  < 0.05) to detect effects of CACNA1C genotype on FA, and its potential interaction with ZNF804A genotype and with diagnosis, on FA. There was no significant main effect of the CACNA1C genotype on FA, nor diagnosis by genotype(s) interactions. Nevertheless, when inspecting SZ in particular, risk allele carriers had significantly lower FA than the protective genotype individuals, in portions of the left middle occipital and parahippocampal gyri, right cerebellum, left optic radiation and left inferior and superior temporal gyri. Our data suggests a minor involvement of CACNA1C rs1006737 in psychosis via conferring susceptibility to white matter microstructural abnormalities in SZ. Put in perspective, ZNF804A rs1344706, not only had a significant main effect, but its SZ‐specific effects were two orders of magnitude more widespread than that of CACNA1C rs1006737. Abstract : Psychosis risk variant for calcium‐channel CACNA1C rs1006737 polymorphism is asociated with decreased microstructural white matter intergity in portions of the left middle occipital and parahippocampal gyri, right cerebelleum, left optic radiation and left inferior and superior temporal gyri, in schizophrenia patients.